Comparison of the chemical profiles of fresh‐raw and dry‐processed Juglans mandshurica. Issue 3 (23rd December 2016) - Huo, Jinhai; Du, Xiaowei; Sun, Guodong; Meng, Yanli; Wang, Weiming
Abstract : The processing of Juglans mandshurica Maxim. is important to reduce its toxicity and enhance its efficacy. Simple, efficient, and sensitive ultra‐high performance liquid chromatography coupled with a time‐of‐flight mass spectrometry based chemical profiling approach was proposed to rapidly evaluate the chemical difference between fresh and dry samples. Under the optimized ultra‐high performance liquid chromatography and quadrupole time‐of‐flight tandem mass spectrometry conditions, 81 significantly different compounds were rapidly discovered using principal component analysis, and then tentatively identified by comparison with reference substances or inferred through mass spectral fragment ion analysis and literature data. These compounds included 35 naphthoquinones, 11 diarylheptanoids, nine flavonoids, eight triterpenes, 12 phenolic acids, and six aliphatics. The results demonstrated that chemical reactions occurring during processing could be used to elucidate the processing mechanism of Juglans mandshurica Maxim. This study provides a novel approach to identifying complicated components of various complex mixtures in fresh‐raw and dry‐processed traditional Chinese medicines, which could be used as a valid analytical method to further understand the processing mechanisms of these medicines, as well as providing intrinsic quality control of the medicines and their processed products.